Paradoxical reaction to IL-17A inhibitor: a case report and literature review - Ren, Jingyu; Deng, Linjun; Guo, Shuping; Liu, Hongye (Frontiers in Medicine, 2024)
Objective A case of pustular psoriasis after treatment with secukinumab in a patient with plaque psoriasis is reported, which is the first case in China. To summarize the clinical characteristics of patients who developed the rare paradoxical reaction and treatment options received IL-17A antagonist therapy, we conducted a further literature review. Methods Data were analyzed from a patient with plaque psoriasis who developed pustular psoriasis after treatment with secukinumab. A comprehensive review of relevant domestic and international literature was conducted, focusing on cases that met our inclusion criteria for analysis and synthesis. Results Anti IL-17A therapy may lead to type conversion, with reported cases more prevalent in women and varying in onset time, predominantly involving palmoplantar pustulosis. Conclusion Given the increasing use of IL-17A antagonists in psoriasis treatment, it is crucial to monitor for rare adverse reactions, including the paradoxical induction of pustular psoriasis.